Yield and quality of strawberry fruit grown in a greenhouse in a pyramidal hydroponic system - Alvarado Chavez, Juan Alberto; Gomez Gonzales, Adrian; Lara Herrera, Alfredo; Díaz Pérez, Juan Carlos; Garcia Herrera, Eduviges Javier (Revista Mexicana de Ciencias Agrícolas, 2020)
Strawberry (Fragaria x ananassa Duchesne) is an important crop in Mexico and the world. To increase yields, various production systems have been explored, such as hydroponic systems. The objective of this study was to determine the effect of strawberry cultivars, planting densities and strata in a pyramidal hydroponic system, on plant development, production and fruit quality. The study was carried out in Salinas de Hidalgo, SLP, Mexico, in the spring-autumn cycle of 2017. The stratum factor impact on the development and yield of the crop, with the high stratum the number of leaves, crown width, increased number of fruits and yield (23.5 kg m-2), and quantity of soluble solids in comparison with the lower ones. The plants in the intermediate strata were less productive, probably due to the shade caused by those in the higher strata. Density and cultivar had no significant effect on fruit development, yield and quality.
Keywords: Fragaria x ananassa Duchesne; greenhouse; plant density; vertical production systems